Upaya Peningkatan Hasil Belajar Biologi Dengan Menggunakan Model Pembelajaran Practice Rehearsal Pairs (Prp) Pada Siswa Kelas Viii B Smp Negeri 3 Colomadu KabupatenKaranganyar Tahun Ajaran 2012/2013 - QOMARIYAH, SITI NURUL (2016)
The purpose of this study was to determine the learning outcome of biology at the motion of matter in plants using cooperative learning model type Practice Rehearsal Pairs in class VIII B of SMP Negeri 3 Colomadu. The population in this study were students of class VIII B as many as 32 students, this study uses a strategy Practice Rehearsal Pairs. The technique of collecting data through observation, interviews, tests, and documentation. Data analysis included data collection, data reduction, data presentation, and conclusion. The results of this research was obtained before the implementation of strategies that students who have not completed KKM as many as 23 students or as many (71.87%), while students who completed KKM or as much as 9 students (28.12%). After the implementation of the strategy PRP, in the first cycle shows that students who have not completed the student as much as 9 percentage (28.12%), while students who completed as many as 22 students KKM percentage (68.75%). In the second cycle shows that students who have not completed KKM students as much as 1 percentage (3, 23%), while students who have completed as many as 31 students percentage (96, 87%). Improved cycle I to cycle II, the percentage is as much as 28.12%. Hypothesis action with the percentage indicator of achievement as much as 96.87% with a value above KKM (≥60). Based on the results of these studies, the conclusion that can be drawn from this study is the learning process using the learning model PRP strategies, can improve learning outcomes on the material motion systems biology in plants, both cognitive and affective aspects. Keywords: cooperative learning, PRP, learning outcomes.